2009
DOI: 10.1371/journal.ppat.1000547
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Processing of a Small Nucleolar RNA from the Epstein-Barr Virus Genome

Abstract: Small nucleolar RNAs (snoRNAs) are localized within the nucleolus, a sub-nuclear compartment, in which they guide ribosomal or spliceosomal RNA modifications, respectively. Up until now, snoRNAs have only been identified in eukaryal and archaeal genomes, but are notably absent in bacteria. By screening B lymphocytes for expression of non-coding RNAs (ncRNAs) induced by the Epstein-Barr virus (EBV), we here report, for the first time, the identification of a snoRNA gene within a viral genome, designated as v-sn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
98
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(103 citation statements)
references
References 72 publications
(91 reference statements)
2
98
1
Order By: Relevance
“…However, the magnitude of the CD8 ϩ T cell response to latent antigens during acute infection is less robust than the response to lytic antigens and peaks during convalescence (29). In vitro, BHRF1 miRNAs have been shown to reduce expression of latent viral proteins in infected B cells, which may facilitate immune evasion of latently infected B cells in vivo (30). B cells infected with the ⌬123 mutant in vitro not only exhibit blood cells (cell-associated DNA) and plasma (cell-free DNA) of WT/REV (n ϭ 10) and ⌬123 (n ϭ 11) virus-exposed mice was determined with real-time PCR.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the magnitude of the CD8 ϩ T cell response to latent antigens during acute infection is less robust than the response to lytic antigens and peaks during convalescence (29). In vitro, BHRF1 miRNAs have been shown to reduce expression of latent viral proteins in infected B cells, which may facilitate immune evasion of latently infected B cells in vivo (30). B cells infected with the ⌬123 mutant in vitro not only exhibit blood cells (cell-associated DNA) and plasma (cell-free DNA) of WT/REV (n ϭ 10) and ⌬123 (n ϭ 11) virus-exposed mice was determined with real-time PCR.…”
Section: Figmentioning
confidence: 99%
“…slower cell growth kinetics but also display increased expression of latent viral proteins compared to their WT/REV virus-infected counterparts (30). Therefore, we next wanted to examine the CD8 ϩ T cell response to EBV infection in the peripheral blood of mice exposed to the WT/REV and ⌬123 viruses.…”
Section: Figmentioning
confidence: 99%
“…However, numerous SNORDs without obvious target RNAs have been identified (7)(8)(9)(10) and are termed "orphan snoRNAs." Genome-wide deep sequencing experiments identified shorter but stable SNORD fragments that were found in all species tested, ranging from mammals to the protozoan Giardia lamblia (11) and EpsteinBarr virus (12). Fragments longer than 27 nt generated by SNORDs will likely not bind argonaute proteins that bind to 21-to 22-nt-long microRNAs.…”
mentioning
confidence: 99%
“…8 Interestingly, v-snoRNA1 exhibits sequence complementarity to the 3'-UTR of the viral DNA polymerase BALF5 mRNA. In addition, it has been demonstrated that v-snoRNA1 is processed into a miRNA-like species, which might target BALF5 mRNA, as it was also reported for EBV-encoded miRNA-BART2.…”
Section: Ncrna-microchip Analysismentioning
confidence: 99%
“…3 Until now, 28 non-protein coding RNA (ncRNA) genes have been mapped to the EBV genome, including Epstein-Barr virus encoded RNAs (EBER) 1 and 2, 4 25 micro-RNAs (miRNAs) [5][6][7] and a single small nucleolar RNA (snoRNA), designated as v-snoRNA1. 8 EBV employs viral encoded small ncRNAs from infection of B cells: for example, EBER 1 binds to double-stranded RNAactivated protein kinase (PKR), a key mediator of the antiviral effect of interferon (IFN)-α. Binding of EBER1 to PKR prevents PKR-mediated phosphorylation of the α-subunit of epstein-Barr virus (eBV) infection of human B cells requires the presence of noncoding RNAs (ncRNAs), which regulate expression of viral and host genes.…”
Section: Introductionmentioning
confidence: 99%